Effects of Artificial Intelligence on the Academic Achievement of Undergraduate Students - Kamran Khan; Dr Samreen Mehmood; Dr Hafiz Muhammad Irshadullah (Dialogue Social Science Review (DSSR), 2025)
This study investigates the effect of Artificial Intelligence (AI) tools on the academic achievement of undergraduate students at AWKUM Garden Campus. With the rapid advancement of AI technologies, educational institutions are increasingly integrating these tools to enhance student learning outcomes. The primary objective of this research is to explore how AI tools, such as ChatGPT, Grammarly, and Google Bard, impact students' academic performance and to understand the relationship between the frequency of AI usage and academic success. The study also aims to analyze how AI tools affect students with varying levels of academic achievement. A quantitative research approach was adopted. A total of 200 students participated in the survey, providing valuable data for analysis. The findings were analyzed using descriptive and inferential statistics to draw meaningful conclusions. The results found that AI tools significantly improve students' academic performance, particularly in tasks such as writing assignments, research work, and exam preparation. The study found a positive relationship between the frequency of AI tool usage and academic achievement, suggesting that students who use AI tools more frequently tend to perform better academically. In conclusion, the study confirms the benefits of AI tools in enhancing academic achievement among undergraduate students. However, it also points to the need for further integration of AI tools into educational settings, along with guidance on how to use them effectively. Future research should explore the long-term effects of AI tool usage, the impact of AI on students with different learning styles, and how AI tools can be adapted for different academic disciplines.